Comparison between Effects of Propofol and Dexmedetomidine as Sedative in Elective Caesarean Section under Subarachnoid Anaesthesia - Karim, Md Enayet Karim; Mostafiz, RAM Mostafizur Rashid; Akram, Mohammad Saleh Akram; Ershad, Reza (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: The use of spinal (subarachnoid) anaesthesia is often limited by the unwillingness of patients to remain awake during surgery. Objective: This study was undertaken to compare propofol and dexmedetomidine in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesarian section under spinal anaesthesia. Methodology: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I patients undergoing elective Caesarean sections under Subarachnoid anaesthesia during the period January 2022 to June 2022. Patients were randomly allocated to one of two groups designated as Propofol group (Group A, n=30), who received Propofol in a single dose of 0.5mg/kg and Dexmedetomidine group (Group B, n=30), who received Dexmedetomidine in a single dose of 2mcg/kg. The onset of sedation i.e. time from iv (intravenous) injection of propofol or dexmedetomidine to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 (patient is awake clinically) were noted. Any complication during operation was documented. Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups in different time intervals (P>0.05). Time of onset of sedation was significantly delayed in Dexmedetomidine group (P<0.05). The arousal time i.e. duration of sedation was significantly longer with Dexmedetomidine than Propofol (P<0.05). Propofol was associated with significantly higher incidence of some adverse effects like pain in arm during drug administration than Dexmedetomidine (46.66% vs 10.0%, P<0.05). Significant percentage of patients was satisfied with dexmedetomidine than propofol (86.66% vs 13.33%, P<0.001). Conclusion: Duration of sedation is significantly longer with dexmedetomidine than propofol which is beneficial for the patient in single dose technique for sedation. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):65-70